The Role of Primary Tumor Resection in Patients With Pancreatic Neuroendocrine Tumors With Liver Metastases - Mou, Yu; Wang, Zi-Yao; Tan, Chun-Lu; Chen, Yong-Hua; Liu, Xu-Bao; Ke, Neng-Wen (Frontiers in Oncology, 2022)
Background Liver metastases (LMs) are common in advanced pancreatic neuroendocrine tumor (PNET) patients. Currently, the benefit of primary tumor resection (PTR) in the setting of PNET patients with liver metastases is still controversial in several guidelines. Methods Data were extracted from the Surveillance, Epidemiology and End Results (SEER) database to evaluate this issue. The main index of interest in our study was overall survival time. Results Information on 536 PNET patients with liver metastases from the SEER database was identified. A total of 214 patients (PTR group) received primary tumor resection, and more than half of them (132 patients) had synchronous LM resection. The other 322 PNET patients (non-PTR group) with liver metastases did not receive primary tumor resection. A significant survival benefit was gained from PTR when compared with non-PTR patients, both in OS (72.93 ± 2.7 vs. 36.80 ± 2.22 months) and 3- or 5-year survival rates (75.1% vs. 28.9% and 67.9% vs. 22.3%, respectively). No difference was found between PTR alone and PTR with synchronous LM resection. From univariate and multivariate analyses, younger age (<65 years) and good or moderate tumor differentiation may be more important when considering primary tumor resection. However, we found that all grades of tumor differentiation could result in a better overall survival time after primary tumor resection. Conclusion Our study suggested that primary tumor resection in pancreatic neuroendocrine patients with liver metastases could result in a longer survival time. Primary tumor resection with synchronous liver metastasis resection was not related to a better survival benefit. This treatment strategy may routinely be taken into consideration in these patients.